The Politics of "Pombilai Orumai": The 2015 Kanan Devan Strike in Kerala, India - Anagha S. (Atlantis)
Colonial hegemony was retained in the South Indian plantations of Kanan Devan Hills Plantations Limited, where the workers belonged to marginalized classes. The landless employees were given housing facilities, and this compelled them to remain there for generations despite poor wages. These uneducated and geographically secluded people found it difficult to come out of the plantation labyrinth, and the labour acts or land legislation acts were not much help. In 2015, around 5,000 women workers called “Pombilai Orumai” led a successful strike for a wage increase. The most remarkable aspect of this was the disassociation with political parties and trade unions and the solidarity of women workers despite all odds.